Anthropologists Engaged with the Law (and Lawyers) - Grillo, Ralph (Antropologia Pubblica, 2024)
The official review of research carried out in British universities in 2014 required departments to present case studies documenting the “impact” (“reach and significance”) of their research beyond the academy. Despite misgivings, anthropology departments presented detailed studies across a range of sub-fields of the discipline which were judged to have demonstrated “productive engagement with publics, users and policy makers”. Some of the studies illustrated a contribution to one field, what Bourdieu called the “judicial field”, which has become increasingly significant for anthropologists across Europe and North America, especially where ethnic, cultural and religious minorities are concerned. The paper examines a number of situations of this kind (including interventions in tribunals assessing the claims of asylum seekers) where anthropologists acting as cultural interpreters or mediators have had to interact with the law and with lawyers and others whose disciplinary mindsets may be very different from their own. While this may be very productive, it also poses numerous dilemmas, not least of which is whether those whom anthropologists seek to address (the powers-that-be) actually listen to what they have to say.